Dairy-draft on-farm performance of crossbred cows in Holetta area - Alemayehu, M.; Gebre-Wold, A.; Tegegne, Azage; Zerbini, E.; Larsen, C. (Ethiopian Society of Animal Production, 1998)
Based on the promising results obtained from on-station, the cow traction study was further taken to on-farm for verification under the Ethiopian smallholder farmers management conditions. The study was undertaken in Holetta area between 1992 and 1996 by involving 14 farmers. Mean dairy milk yield was similar between working (5.08 kg) and non-working (5.58 kg) crossbred cows that were kept under smallholder farm management conditions. Lactation yield of non-working cows was significantly higher (2103.57 versus 1725.17 kg) than that of working cows. This difference emanated from lactation length where non-working cows had exhibited significantly longer lactation length. Mean milk composition of working and non-working cows was similar in fat, protein and total solid contents. Working cows were observed to lose more weight after calving than non-working cows at both onset of first postpartum estrus and conception though not statistically significant. There were no significant differences between working and non-working crossbred cows in mean intervals of calving to first postpartum estrus and calving to conception. The interval from first estrus to conception after second calving was shorter than during first calving where working and non-working cows conceived about 42 and 32 days, respectively, after exhibiting first estrus. This suggests that postpartum anestrus was a more important problem than conception failure during the second than the first calving period. In general, the crossbred cows have been in negative energy balance as this was seen from their body weight loss over the most period of the year (March to end of October). It was concluded that as long as improved feeding management and lower level of work are coupled, it is unlikely for traction to have adverse effect on productive and reproductive performances of crossbred dairy cows.